The Impact of Digital Financial Trading on Investor Behavior In Traditional Financial Markets - Haider Abbas abdullah Aljanabi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Based on the great development that has included all aspects of life, including financial investment, and with the entry of technology with all its strength in facilitating business, great thought has begun to be given to explaining how technology affects investor behavior when entering the securities market. The research dealt with a digital platform (Trader4) and its impact on attracting investors to invest through it. The results showed that digital platforms have a great impact on investor behavior by providing many services that facilitate work for the investor, which prompted many investors to resort to digital platforms and invest through them and leave traditional markets. This gave indications that digital platforms have changed investor behavior through the attraction factors that they used towards the investor. The research presented a set of recommendations, the most important of which was to work on raising awareness and understanding among investors through the media and publishing on how to choose the right path in building their financial investments and using technology in its forms that help build society financially and investment-wise.